PENGARUH DUKUNGAN APARAT DESA DAN KOMITMEN ANGGOTA TERHADAP PROGRAM KERJA KARANG TARUNA - Zumrawi Zumrawi; Irawan Suntoro; Yunisca Nurmalisa (Jurnal Kultur Demokrasi, 2015)
The purpose of this research was to explain the effects of Villages Agency Support and Neighborhood Youth Association members commitment toward organization program of Neighborhood Youth Association in village of SimpangAsam, subdistrict of Banjit, regency of Waykanan in 2015. Research method used in this research was associative-quantitative method with descriptive ex post facto approach.The result of this research showsed that: (1) There was0 a significant effect between Villages Agency support (X1) toward organization program of Neighborhood Youth Association (Y). (2)there is a significant influence between the commitment of neighborhood youth Association member (X2) toward organization program of Neighborhood Youth Association (Y). (3) There is also a significant effect between village agencys support (X1) And Neighborhood Youth Association members commitment (X2) There is a significant influenc between the commitment of nigh borhood youth association member(Y).Tujuan penelitian ini untuk menjelaskan pengaruh dukungan aparat desa dan komitmen anggota karang taruna terhadap program kerja karang taruna di desa simpang asam kecamatan banjit kabupaten waykanan tahun 2015. Metode penelitian yang digunakan dalam penelitian ini adalah jenis penelitian kuantitatif asosiatif dengan pendekatan deskriptif ex post facto. Hasil penelitian ini menunjukkan bahwa: (1) Terdapat pengaruh yang signifikan antara dukungan aparat desa (X1) terhadap program kerja karang taruna (Y). (2) Terdapat pengaruh yang signifikan antara komitmen anggota karang taruna (X2) terhadap program kerja karang taruna (Y). (3) Terdapat pengaruh yang signifikan antara dukungan aparat desa (X1) dan komitmen anggota karang taruna (X2) terhadap program kerja karang taruna (Y).Kata kunci: dukungan aparat desa, komitmen anggota karang taruna, program kerja karang taruna